SPACE CHARGE MEASUREMENT TECHNIQUE FOR FULL SCALE CABLE AT HIGH CONDUCTOR TEMPERATURE - Sumarwoto, Trinurkalid
Background. Polymer insulated HVDC power cable is being employed for submarine transmission with long distance. Its insulation may produce internal space charge, which cause a distortion of electrical field. Moreover, since the insulation is subjected to a high temperature originating from the current in the conductor, space charge can be easily injected to the insulation. In the development process of cables, it is very substantial to prove that no significant space charge is formed. The space charge measurement for full-scale cable is preferable at the final stage of the development. One of the powerful tools for space charge measurement is Pulse Electro-Acoustic (PEA) method. In this study, the equipment for space charge measurement in full size cable was modified to obtain high temperature conductor by Current Transformer (CT) and the space charge distribution was investigated at high conductor temperature. We proposed a method to estimate the conductor temperature for the result of the charge distribution. Experimental method. Space charge measurement at high conductor temperature is applied for a full-sized model cable with the construction of 3 mm polymer insulation thickness, 1.025 mm for outer semiconductor, 1.05 mm for inner semiconductors and conductor diameter 14.35 mm. A high current at the conductor is generated by adjusting the current flowing through the CT and it heat up the cable up to 361K. Then, space charge is measured by using a PEA technique at high conductor temperature. Results and Discussion. Space charge distribution was investigated by applying the 30 kV DC at room temperature or high conductor temperature. From the detection time difference between the signal of the conductor and ground electrode, sound speed for XLPE at room temperature is 2,069 m/s. The detection time difference at high conductor temperature became more longer than that at room temperature. Assuming that the change of the detection time difference caused by changing the sound speed of XLPE at high conductor temperature, the speed of XLPE at high conductor temperature can be estimated to be approximately 1,810 m/s. The conductor temperature corresponding to this sound speed change can be estimated as 358.15 K. This estimated conductor temperature is almost the same as the measured one 360.15 K by thermocouple. It was suggested that the conductor temperature can be estimated by space charge measurement without directly measuring the conductor temperature. Since space charge measurement for full size cable in conventional research has been performed at room temperature, the space charge accumulation cannot be evaluated. Space charge is significantly accumulated at high conductor temperature and its phenomena can be investigated by using the developed equipment.